Leopardus wiedii Papillomavirus type 1, a novel papillomavirus species in the tree ocelot, suggests Felidae Lambdapapillomavirus polyphyletic origin and host-independent evolution - Dolz, Gaby (2020)
The limited knowledge on Papillomavirus diversity (particularly in wild animal species) influences the accuracy of PVs phylogeny and their evolutionary history, and hinders the comprehension of PVs pathogenicity, especially the mechanism of virus - related cancer progression. This study reports the identification of Leopardus wiedii Papillomavirus type 1 (LwiePV1), the first PV type within Lambdapapillomavirus in a Leopardus host. LwiePV1 full genome sequencing allowed the investigation of its taxonomic position and phylogeny. Based on results, LwiePV1 should be assigned to a novel PV species providing evidence for a polyphyletic origin of feline lambda PVs, and representing an exception to codivergence between feline lambda PVs and their hosts. Results improve our knowledge on PV diversity and pave the way to future studies investigating biological and evolutionary features of animal PVs.